An Al–Si–Ti hierarchical metal–metal composite manufactured by co-spray forming - Kelly, A. J. (2011)
Spray forming with co-injection of a solid particulate phase to form a homogeneous distribution within the final spray formed billet has been studied as a new route to manufacturing metal–metal composites at large scale with negligible oxide. 12 wt%Ti particles were co-injected into an atomised Al alloy droplet spray and co-deposited to form a ∼300 kg billet at Peak Werkstoff GmbH, Germany. The microstructure comprised refined equiaxed α-Al grains (∼5 μm), spherical Si particles (∼1 μm) and uniformly distributed Ti particles (∼80 μm). Sections of the billet were extruded under a range of conditions into long strips 20 mm wide and 6 mm, 2.5 mm and 1 mm thickness. At high strains, the Ti particles were deformed into continuous fibres of a few microns in thickness. The large interfacial area between the fcc α-Al and hcp Ti inhibited dislocation motion and enhanced tensile properties. Accumulative roll bonding was then performed to higher total strains, while maintaining a constant cross-section, reducing the Ti fibres to sub-micron thickness. The fibres were studied by extraction after selective dissolution of the α-Al matrix. There was no interfacial reaction between α-Al and Ti or any measurable oxide formation.